Racial Attitudes in Wartime: The @Protestant Churches during the Second World War - Orser, W. Edward (Church history, 1972)
Delegates to a special meeting of the Federal Council of Churches in Columbus Ohio, in March, 1946, adopted a report which committed the Council to work for a non-segregated church in a non-segregated society and called upon its constituent communions to do likewise. The statement represented a new departure, but its timing—coming at the end of the Second World War—was also significant. Although the position of the Federal Council was in advance of any positain yet taken by the major protestant denominations individually, it indicated that American protestantism was beginng to be challenged in a new way by the question of race. In the yers immediately prior to 1939 the denominations paid little attention to race as a social issue: by 1945 it was frequently the subject of denominational pronouncements and editorials in the church press. This contrast in the reponse of the churches suggests that the years of the Second World War had been crucial in placing new pressures upon white attitudes toward black Americans.